MiR-629-5p Promotes Prostate Cancer Development and Metastasis by Targeting AKAP13 - Liu, Yangzhou; Zhao, Shankun; Wang, Jiamin; Zhu, Zhiguo; Luo, Lianmin; Xiang, Qian; Zhou, Mingda; Ma, Yuxiang; Wang, Zuomin; Zhao, Zhigang (Frontiers in Oncology, 2021)
Prostate cancer (PCa) has become the most frequently occurring cancer among western men according to the latest report, and patients' prognosis is often poor in the event of tumor progression, therefore, many researches are devoted to exploring the molecular mechanism of PCa metastasis. MicroRNAs (miRNA) have proved to play an important role in this process. In present study, by combining clinical samples with public databases, we found that miR-629-5p increased to varying degrees in primary localized PCa tissues and metastatic PCa tissues compared with adjacent normal tissues, and bioinformatics analysis suggested that high level of miR-629-5p was related to poor prognosis. Functionally, miR-629-5p drove PCa cell proliferation, migration and invasion in vitro, and promoted growth of PCa cells in vivo. Moreover, A-kinase Anchor Protein 13 (AKAP13) was screened as a direct target of miR-629-5p, that expression was negatively correlated with the malignant phenotype of tumor cells. In the end, through verification in clinical specimens, we found that AKAP13 could be independently used as a clinical prognostic indicator. Overall, the present study indicates that miR-629-5p plays an oncogenic role in PCa by targeting AKAP13, which provides a new idea for clinical diagnosis and treatment of complex refractory PCa.